A Comparative Study of Systolic Blood Pressure, Diastolic Blood Pressure, Mean Arterial Pressure and Pulse Pressure between Urban and Rural Population (International Journal of Physiology, 2019)
Hypertension is a commonest cardiovascular disorder affecting more than 30% of the adult population in many countries. It is considered to be one of the important risk factor for cardiovascular disease, diabetes, stroke and CKD. It is projected that by the year 2020 it will cause a global burden.17. It is seen that death and disability from coronary heart disease and CKD are increasing so quickly that the public health authorities are facing a challenge in controlling it. New research has shown that the risk of brain lesions was higher in people with higher average systolic pressure. Researchers discovered increased biomarkers for Alzheimer's in the brains of older patients with high blood pressure. 21. Obstructive sleep apnea 3 is also associated with hypertension. The M.A.P and P.P both are associated with ischemic stroke 4. MAP is a critical hemodynamic factor in the regulation of blood pressure, an inadequate flow to organs may cause syncope and shock. It is seen that rise in blood pressure has become a major risk factor for premature disability and death worldwide. Taking into consideration all of the above factors and the different life styles of the urban and rural population this study was under taken. A total of 200 subjects were included in the present study. In this study we measured the S.B.P, D.B.P, M.A.P and P.P. It was noticed that there was a significant rise in systolic and diastolic blood pressure as well as the mean arterial pressure and the pulse pressure in the urban population compared to the rural population.